2002
DOI: 10.1111/j.1468-2885.2002.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Audience Involvement and Entertainment?Education

Abstract: The present article explores the role that audience involvement plays in the effectiveness of entertainment—education programs. Utilizing data from a popular 104—episode entertainment—education radio soap opera from India, Tinka Tinka Sukh, it argues that the concept of audience involvement is multidimensional, and serves as a mediator for promoting behavior change. Audience involvement is characterized as being composed of two dimensions: (a) affective—referential involvement, and (b) cognitive—critical invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 41 publications
2
77
2
3
Order By: Relevance
“…The dramatic arts and song let performers become the vehicle for conveying the message. For some, participation has proven itself to be ''the critical element for effecting change'' (Sood 2002). After all, as MacKinnon (2008) points out, health communication theory implies that entertainment-education is essentially participatory in nature, and as its 'motto' suggests: ''sing and the world sings with you.…”
Section: Fundamentals Of Entertainment-educationmentioning
confidence: 99%
“…The dramatic arts and song let performers become the vehicle for conveying the message. For some, participation has proven itself to be ''the critical element for effecting change'' (Sood 2002). After all, as MacKinnon (2008) points out, health communication theory implies that entertainment-education is essentially participatory in nature, and as its 'motto' suggests: ''sing and the world sings with you.…”
Section: Fundamentals Of Entertainment-educationmentioning
confidence: 99%
“…The way in which narrative influences in attitude and behaviour of viewers have been analysed by many researchers; however, most of the works have been based on traditional media: television, film and radio (Moyer-Gusé, 2008; Sood, 2002). The aim of this study was to examine the efficacy of narrative in new media, such as social networks.…”
Section: The Importance Of the Narrative Formatmentioning
confidence: 99%
“…Involvement with the character increases attention span, serves as a mental rehearsal and models behaviour (Sharf, Freimuth, Greenspon, and Plotnick, 1996;Sood, 2002). Some authors define it as the spectator assuming the role of a character and substituting their identity as an audience member with that of the character (Cohen, 2001).…”
Section: Involvement With the Charactermentioning
confidence: 99%
See 1 more Smart Citation
“…Entertainment-education research has found that feeling similar to characters, or adopting characters' perspective while viewing, can increase self-efficacy and positively impact story-consistent attitude and behavioral intentions (Green, Brock, & Kaufman, 2004;Sood, 2002;Wilkin, Valente, Murphy, Cody, Huang, & Beck, 2007). The E-ELM (Slater & Rouner, 2002) posits that identification and transportation function similarly in narrative persuasion.…”
Section: Future Researchmentioning
confidence: 99%